Proyecto de factibilidad para la implementación de una pista de Bowling (bolos) en la cuidad de Loja, provincia de Loja - Cueva Ordoñez, Katherine Denisse (2023)
The scope of this research paperwork is to conduct a feasibility study for the startup of a bowling alley, in the city of Loja, province of Loja. We focused it on the entertainment services market, which allows people to have fun. The specific objectives were to determine the feasibility of the market, technical, administrative, and financial study. The type of research is descriptive with a mixed approach. The study population that we took into consideration are the economically active people of the city of Loja; through descriptive analysis, we collected the necessary information; the market study allowed us to specify an unsatisfied demand of 21.249 games; the technical study determined the installed capacity of 22.320 games per year, with four bowling lanes installed; the administrative research study established that the human talent required would be composed of 6 people; the economic research study allowed the calculation of the total investment requirement at $57,370.29; the price of the service will be $5.00 in the first year and $6.00 in the fifth year. In the first year, we should use a capacity of 46.66%, and we should need to sell 40,561.48 services to cover expenses. The present work yields a positive NPV of 79,054.96, an IRR of 50.72%, an RBC of $0.70, and the capital recovery period is two years, three months, and nine days as for the sensitivity analysis, it supports an increase of 33.17% and a decrease of 33.15%, by employing these indicators we deduced that the Project is feasible and, we recommended to take into consideration the specifications established in the research of the Project carried out.